The influence of sexual objectification on guilt assessment on a sample of Italian graduates. Issue 2 (12th July 2021) - Cabras, Cristina; Tumatis, Roberta; Mondo, Marina; Sechi, Cristina
Abstract : Purpose: The purpose of this study was to investigate the influence of sexual objectification on the attribution processes of the guilt of a defendant – and also on the level of guilt. It was also hypothesized that legal expertise could be a protective factor in countering the influence of sexual objectification. Design/methodology/approach: Sexual objectification can be defined as the perspective in which a person is evaluated solely in terms of his or her body parts or sexual function. As yet, no studies have assessed the influence of sexual objectification on guilt assessment in the legal system; this paper aims to explore whether sexual objectification has an influence on the attribution processes of a defendant's guilt. Findings: The statistical analysis revealed that the sexually objectified defendant received a guilty verdict more often than a non-sexually objectified defendant; additionally, legal experts were more likely to identify the defendant as not guilty than non-legal experts. The findings support the hypothesis that sexual objectification is indeed one of the common stereotypes that lead to discrimination. Originality/value: The present study provides novel findings regarding sexual objectification in the forensic context in which the defendant is viewed and evaluated.